Counsellors Practices of Ethnic and Religious Factors in Secondary Schools - Mohamed Sharif, Mustaffa; Amalia, Madihie; Prashanth, Talwar Yadar; Aqeel, Khan (2017)
This study explored the everyday experiences of Muslims’ school counsellors as they encounter and negotiate ethnic and religious contextual factors in their practices in Malaysian secondary schools. Specially, the study also explored how Muslims’ school counsellors adapt their generic, Western-oriented training models and practices to the needs of everyday practice in Malaysian society. In particular, the researcher investigated the influence of multi-ethnicity of students and diversity of religion in their counselling contexts. A major difficulty is that much of the literature appears to be general, theoretical or ideological, rather than based on the actual experiences of practicing counsellors in the countries concerned. In order to focus on experience of counsellors, a qualitative case study approach was used. The researcher examined the practice of eleven Muslims’ school counsellors in the district of Muar, using a combination of interviews, observation and document analysis. The data suggested that counsellors actively adapt their training models in various ways in relation to the two factors studied. Counsellors perceived a considerable gap between what they learned in their university training course and the knowledge and skills required for actual practice